DETERMINATION OF LEAD ACCUMULATION BY LEAVES OF DIFFERENT VEGETATION, GROW IN SOIL POLLUTION - Alushllari, Mirela; Civici, Nikolla (European Scientific Journal, ESJ, 2014)
Both natural and anthropogenic contributions are the sources of leademissions to the environment. Lead is easily accumulated in the edible partsof leafy vegetables, as compared to grain or fruit crops. The accumulation oflead in agricultural soils is potentially hazardous to human, livestock andplants species. The purpose of this study is: determination of lead in soil anddifferent spontaneous plant species grown it, as well as calculation ofdeterminate bioaccumulation factors (BAF) soil to plant. We have selected21 sampling point at a distance 80-600 m around Former Factory Productionof Batteries to Berat, Albania. We have collected a total of 42 samples where21 are soil samples and 21 are vegetation samples. All the representativesamples for this study were analyzed using Atomic Absorption Spectrometryfor their lead content, at the Institute of Applied Nuclear Physics, Universityof Tirana, Albania. From results obtained, the concentrations of lead inrepresentative soil samples were found in the levels: 126 mg/kg-24207mg/kg while in the biological samples, the levels of lead were: 0.238-4.572mg/kg. The concentration ranges of lead in soil samples collected at differentpoints are compared with the Maximum Contaminant Levels (MCL)recommenced by European Union according the Directive 86/278/EEC.Also, we have calculated Hazardous Quoted (HQ) for each sampling point ofsoil. The concentration ranges of lead in biological samples collected arecompared with the Maximum Contaminant Levels (MCL) specified by theDirective No. 1881/2006, Brussels. Concentrations of lead were measuredalso in surface soil, near the root of plant species, in one of the most pollutedareas in Albania, Uznove, Berat. Also we have calculated bio accumulationfactor (BAF) soil to plant.